Graphite negative electrode material, preparation method, pole piece and battery
By using the reduction of iron powder catalysts at 1500 ° C, thermal solution oil is converted into biological graphite, which solves the problem of high traditional graphite preparation costs and environmental pollution, realizes the low -cost and safe graphite preparation process, and improves electrochemical performance.
Patent Information
- Application Number
- CN202411520188.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, there are problems such as high cost of graphite preparation, difficulty in operation, low productivity and raw material safety, especially when using sulfur-containing petroleum slag as raw material, the environmental pollution is heavy.
Under 1500 ° C, the reducing iron powder is used as a catalyst, and the thermal solution oil is converted into a biological graphite. By adjusting the content of thermal decomposition and fixing carbon, it can be prepared to achieve different graphite of bioal graphite.
Realize the low cost, simple operation and raw materials of graphite preparation, and simultaneously regulate the electrochemical performance, and obtain a biological graphite negative material with good Kulun efficiency, reversible capacity, cyclicity, and power capacity.
Smart Images

Figure BDA0005107920160000101 
Figure HDA0005107920170000011 
Figure HDA0005107920170000012
Abstract
Description
Technical Field
[0001] The invention relates to graphite negative electrode material, preparation method, pole piece and battery Background Art
[0002] Lithium-ion batteries (LIBs) have attracted widespread attention due to their high energy density, high Coulombic efficiency, extremely low self-discharge rate, negligible memory effect, high open circuit voltage and long service life. The commercially commonly used LIB negative electrode material is graphite because it has many advantages, such as excellent gravimetric capacity (theoretical maximum value of 372mAh / g), low redox potential of about 0.1V (relative to lithium / lithium), long cycle life and low voltage hysteresis, thus achieving high voltage and energy efficiency. Lithium-ion batteries usually have artificial graphite and natural graphite. Traditionally, synthetic graphite is produced from low-sulfur petroleum distillation residues (petroleum coke and coal tar pitch) through several high-temperature steps, including delayed coking (500℃), calcination (1200℃) and graphitization (3000℃). This method has low productivity, high cost and heavy environmental pollution caused by using sulfur-containing petroleum residues as raw materials, so it is urgent to find alternative routes and raw materials for artificial graphite. Two mechanisms have been proposed for catalytic graphitization: (i) dissolution-precipitation mechanism and (ii) formation-decomposition mechanism. According to the first mechanism, amorphous carbon (formed during biomass pyrolysis) first dissolves into molten metal or metal carbide and then precipitates as graphite. According to the second mechanism, carbon forms a carbide intermediate with metal, which decomposes at a certain temperature to leave graphite. The type and amount of catalyst greatly affect the quality of the product.
[0003] Currently, a variety of carbonaceous raw materials have been catalytically converted into graphite at moderate temperatures, including petroleum coke, anthracite, hardwood, softwood, lignin, cellulose, etc., but there has been no research on the catalytic graphitization of pyrolysis oil. Pyrolysis oil is a dark brown liquid containing a variety of oxygenated compounds (alcohols, acids, aldehydes, ketones, sugars, esters, ethers, phenols, furans, etc.). Due to its low calorific value and high water content, it is rarely used, but the high carbon content in pyrolysis oil has prompted the conversion of pyrolysis oil into various types of carbon materials. Considering the large-scale production of battery-grade graphite, pyrolysis oil as a raw material has many advantages over biomass, such as high carbon density, low inorganic matter, easy handling and low transportation cost. Summary of the invention
[0004] At present, in the field of catalytic graphitization, there is no research on the use of pyrolysis oil as a carbonaceous material to prepare graphite in the prior art. In order to solve the problems of high cost, difficult operation, low productivity and raw material safety of graphite preparation in the prior art, the present invention provides a method for converting pyrolysis oil into bio-graphite at 1500°C using reduced iron powder as a catalyst, and assembles a battery for relevant performance tests. The present invention prepares bio-graphite negative electrode materials with different graphitization degrees by adjusting the content ratio of pyrolysis oil and fixed carbon, realizes a simple operation, low cost and raw material safety preparation process, and achieves the purpose of synchronously regulating electrochemical performance.
[0005] The present invention solves the above technical problems through the following technical solutions.
[0006] In a first aspect, the present invention provides a method for preparing a graphite material, which comprises the following steps:
[0007] Under the action of the catalyst, the pyrolysis oil is subjected to graphitization reaction. The solid carbon content of the pyrolysis oil is 32%-67%; the mass ratio of the catalyst to the solid carbon content of the pyrolysis oil is (0.5-3):1.
[0008] In a certain embodiment, the mass ratio of the catalyst to the solid carbon content of the pyrolysis oil is preferably (1-3):1, for example, 2:1.
[0009] The method for determining the fixed carbon content of the pyrolysis oil is as follows: 3 g of the pyrolysis oil is placed in an oxidation furnace crucible, and the temperature is rapidly raised to 1200°C (10°C / min) in a tubular furnace at a nitrogen flow rate of 100 ml / min. The temperature is kept at 1200°C for 1 hour, and the remaining sample mass is weighed after natural cooling to room temperature. The fixed carbon content of the pyrolysis oil is then obtained by dividing the remaining sample mass after high-temperature carbonization by the mass before carbonization (3 g).
[0010] In one embodiment, the catalyst is iron powder particles.
[0011] In one embodiment, the particle size of the iron powder is ≤10 μm.
[0012] In a certain embodiment, the solid carbon content of the pyrolysis oil is 32%-67%, preferably 49.3%.
[0013] In one embodiment, the reaction is carried out in a tube furnace.
[0014] In one embodiment, the reaction is carried out under an inert atmosphere, preferably nitrogen.
[0015] In one embodiment, the reaction temperature comprises the following heating steps:
[0016] Raise the temperature from 25°C to 600°C at a rate of 4°C / min; raise the temperature from 600°C to 1500°C at a rate of 2°C / min, and keep at 1500°C for 1 hour; lower the temperature from 1500°C to 600°C at a rate of 2°C / min; lower the temperature from 600°C to 25°C at a rate of 4°C / min.
[0017] In one embodiment, the graphitization reaction further includes the following post-processing steps: crushing, acid leaching, filtering, washing, and drying.
[0018] In one aspect, the acid leaching uses an acid conventional in the art, preferably hydrochloric acid. The concentration of the hydrochloric acid is 20%-37wt%, preferably 37wt%.
[0019] In one embodiment, the filtering method is vacuum filtration.
[0020] In one embodiment, the cleaning method is cleaning with deionized water.
[0021] In a certain embodiment, the number of cleanings is 3-5 times, for example 3 times.
[0022] In one embodiment, the volume ratio of the cleaning amount to the filtered sample solution is (2.5-3.5:1, for example, 3:1.
[0023] In one embodiment, the acid leaching time is 11-13 hours, for example, 12 hours.
[0024] In one embodiment, the acid leaching temperature is 15-40°C.
[0025] In a certain embodiment, the drying temperature is 75-85°C, preferably 80°C.
[0026] In a certain embodiment, the drying time is 3-5 hours, preferably 4 hours.
[0027] In a certain scheme, the reaction conditions are as follows: take pyrolysis oil and iron powder particles with a corresponding fixed carbon content of 0.5 times, stir and mix them evenly; place the mixed sample in a tubular furnace for graphitization reaction under a nitrogen atmosphere, and the reaction temperature includes the following heating steps: heating from 25°C to 600°C at a rate of 4°C / min, heating from 600°C to 1500°C at a rate of 2°C / min, keeping at 1500°C for 1 hour, cooling from 1500°C to 600°C at a rate of 2°C / min, and cooling from 600°C to 25°C at a rate of 4°C / min; after the reaction is completed, the sample is crushed in a mortar, acid-leached with concentrated hydrochloric acid at 15-40°C for 12 hours, the iron powder is dissolved, filtered with a vacuum filter, washed with deionized water 3 times, and dried at 80°C for 4 hours.
[0028] In a certain scheme, the reaction conditions are as follows: take pyrolysis oil and iron powder particles with a corresponding fixed carbon content of 1 times, stir and mix them evenly; place the mixed sample in a tubular furnace for graphitization reaction under a nitrogen atmosphere, and the reaction temperature includes the following heating steps: heating from 25°C to 600°C at a rate of 4°C / min, heating from 600°C to 1500°C at a rate of 2°C / min, keeping at 1500°C for 1 hour, cooling from 1500°C to 600°C at a rate of 2°C / min, and cooling from 600°C to 25°C at a rate of 4°C / min; after the reaction is completed, the sample is crushed in a mortar, acid-leached with concentrated hydrochloric acid at 15-40°C for 12 hours, the iron powder is dissolved, filtered with a vacuum filter, washed with deionized water 3 times, and dried at 80°C for 4 hours.
[0029] In a certain scheme, the reaction conditions are as follows: take pyrolysis oil and iron powder particles with a corresponding fixed carbon content of twice, stir and mix them evenly; place the mixed sample in a tubular furnace for graphitization reaction under a nitrogen atmosphere, and the reaction temperature includes the following heating steps: heating from 25°C to 600°C at a rate of 4°C / min, heating from 600°C to 1500°C at a rate of 2°C / min, keeping at 1500°C for 1 hour, cooling from 1500°C to 600°C at a rate of 2°C / min, and cooling from 600°C to 25°C at a rate of 4°C / min; after the reaction is completed, the sample is crushed in a mortar, acid-leached with concentrated hydrochloric acid at 15-40°C for 12 hours, the iron powder is dissolved, filtered with a vacuum filter, washed with deionized water 3 times, and dried at 80°C for 4 hours.
[0030] In a certain scheme, the reaction conditions are as follows: take pyrolysis oil and iron powder particles with a corresponding fixed carbon content of 3 times, stir and mix them evenly; place the mixed sample in a tubular furnace for graphitization reaction under a nitrogen atmosphere, and the reaction temperature includes the following heating steps: heating from 25°C to 600°C at a rate of 4°C / min, heating from 600°C to 1500°C at a rate of 2°C / min, keeping at 1500°C for 1 hour, cooling from 1500°C to 600°C at a rate of 2°C / min, and cooling from 600°C to 25°C at a rate of 4°C / min; after the reaction is completed, the sample is crushed in a mortar, acid-leached with concentrated hydrochloric acid at 15-40°C for 12 hours, the iron powder is dissolved, filtered with a vacuum filter, washed with deionized water 3 times, and dried at 80°C for 4 hours.
[0031] In a second aspect, the present invention provides a graphite material prepared by the method for preparing the graphite material as described above.
[0032] In one embodiment, when the mass percentage of the iron powder particles and the solid carbon content of the pyrolysis oil is 2:1, the initial reversible capacity of the graphite material is 345-360 mAh / g, for example, 350 mAh / g.
[0033] In a certain embodiment, when the mass percentage of the iron powder particles and the solid carbon content of the pyrolysis oil is 2:1, the first charging capacity of the graphite material is 90-92%, for example, 90.2%.
[0034] In a third aspect, the present invention provides a use of the graphite material as described above as a negative electrode material.
[0035] In a fourth aspect, the present invention provides a pole piece comprising the graphite material as described above.
[0036] In a fifth aspect, the present invention provides a battery comprising the pole piece as described above.
[0037] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0038] The reagents and raw materials used in the present invention are commercially available.
[0039] The positive and progressive effects of the present invention are:
[0040] Bio-graphite with battery-grade quality is produced using pyrolysis oil derived from renewable and sustainable precursor biomass, and its conversion process is carried out using iron as a catalyst. Compared with traditional methods, this catalytic graphitization based on catalyst iron powder under moderate conditions (1500°C) has multiple advantages such as reduced costs and environmental impact. After graphitization, the residual catalyst can be removed by hydrochloric acid reflux treatment to obtain pure and impurity-free biomass graphite. The graphite sample showed good coulombic efficiency, reversible capacity, cyclability and rate capability in lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Schematic diagram of the process for preparing graphite negative electrode materials
[0042] Figure 2 X-ray diffraction patterns of artificial graphite of the embodiments and comparative examples are shown in FIG.
[0043] Figure 3 Raman test images of the embodiments and comparative examples
[0044] Figure 4 The first and second discharge-charge curves of the artificial graphite negative electrode material prepared in Example 3
[0045] Figure 5 The cycle life of the artificial graphite negative electrode material prepared in Example 3
[0046] Figure 6 The cycle life of the artificial graphite negative electrode material prepared in Example 3 at different discharge rates DETAILED DESCRIPTION
[0047] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0048] In the examples, unless otherwise specified, room temperature refers to 15-40°C.
[0049] The raw materials and catalyst information used in the following examples are as follows:
[0050] Pyrolysis oil: Chongqing Jiuxiang Chemical Rubber Technology Co., Ltd.; fixed carbon content: about 49.3%.
[0051] Iron powder particles: Shanghai Jizhi Biochemical Technology Co., Ltd.; batch number: I27349.
[0052] The method for determining the fixed carbon content of pyrolysis oil is a conventional calculation method in the art: 3g of pyrolysis oil is placed in an oxidation furnace crucible, and the temperature is rapidly raised to 1200°C (10°C / min) in a tubular furnace at a nitrogen flow rate of 100ml / min. Keep the temperature at 1200°C for 1 hour, and weigh the remaining sample mass after natural cooling to room temperature, and then calculate the remaining sample mass after high-temperature carbonization divided by the mass before carbonization (3g) to obtain the fixed carbon content.
[0053] Example 1
[0054] (1) Take 10 g of pyrolysis oil and iron powder particles with a fixed carbon content of 0.5 times the corresponding content, and stir them thoroughly to mix them evenly.
[0055] (2) The mixed sample was placed in a tubular furnace for graphitization under a nitrogen atmosphere. The heating and cooling process was as follows: 25-600°C at 4°C / min; 600-1500°C at 2°C / min; keeping at 1500°C for 1 hour; 1500-600°C at 2°C / min; 600-25°C at 4°C / min.
[0056] (3) Collect the graphitized material and grind it in a mortar.
[0057] (4) The crushed material is acid-leached using concentrated hydrochloric acid (37 wt %) at room temperature to dissolve the iron powder.
[0058] (5) After acid washing, the graphite sample and solution are filtered out using a vacuum filter.
[0059] (6) The filtered sample was washed three times with ultrapure water and then dried at 80 °C for 4 h to obtain the final sample.
[0060] The method for determining the fixed carbon content of pyrolysis oil is to take 3g of pyrolysis oil and place it in an oxidation furnace crucible, and quickly heat it to 1200℃ (10℃ / min) in a tube furnace at a nitrogen flow rate of 100ml / min. Keep it at 1200℃ for 1 hour, naturally cool it to room temperature, weigh the remaining sample mass, and then calculate the remaining sample mass after high-temperature carbonization divided by the mass before carbonization (3g) to obtain the fixed carbon content of the pyrolysis oil.
[0061] Figure 1 This is a schematic diagram of the process of preparing graphite negative electrode materials. Among them: 1. pyrolysis oil; 2. iron powder; 3. tubular furnace; 4. pickling process; 5. cleaning process; 6. final graphitized product; applied lithium-ion battery.
[0062] Example 2
[0063] (1) Take 10 g of pyrolysis oil and iron powder particles with a fixed carbon content of 1 times the corresponding content, and stir them thoroughly to mix them evenly.
[0064] (2) The mixed sample was placed in a tubular furnace for graphitization under a nitrogen atmosphere. The heating and cooling process was as follows: 25-600°C at 4°C / min; 600-1500°C at 2°C / min; keeping at 1500°C for 1 hour; 1500-600°C at 2°C / min; 600-25°C at 4°C / min.
[0065] (3) Collect the graphitized material and grind it in a mortar.
[0066] (4) The crushed material is acid-leached using concentrated hydrochloric acid (37 wt %) at room temperature to dissolve the iron powder.
[0067] (5) After acid washing, the graphite sample and solution are filtered out using a vacuum filter.
[0068] (6) The filtered sample was washed three times with ultrapure water and then dried at 80 °C for 4 h to obtain the final sample.
[0069] Example 3
[0070] (1) Take 10 g of pyrolysis oil and iron powder particles with a fixed carbon content twice that of the pyrolysis oil, and stir them thoroughly to mix them evenly.
[0071] (2) The mixed sample was placed in a tubular furnace for graphitization under a nitrogen atmosphere. The heating and cooling process was as follows: 25-600°C at 4°C / min; 600-1500°C at 2°C / min; keeping at 1500°C for 1 hour; 1500-600°C at 2°C / min; 600-25°C at 4°C / min.
[0072] (3) Collect the graphitized material and grind it in a mortar.
[0073] (4) The crushed material is acid-leached using concentrated hydrochloric acid (37 wt %) at room temperature to dissolve the iron powder.
[0074] (5) After acid washing, the graphite sample and solution are filtered out using a vacuum filter.
[0075] (6) The filtered sample was washed three times with ultrapure water and then dried at 80 °C for 4 h to obtain the final sample.
[0076] Example 4
[0077] (1) Take 10 g of pyrolysis oil and iron powder particles with a fixed carbon content three times that of the corresponding pyrolysis oil, and stir them thoroughly to mix them evenly.
[0078] (2) The mixed sample was placed in a tubular furnace for graphitization under a nitrogen atmosphere. The heating and cooling process was as follows: 25-600°C at 4°C / min; 600-1500°C at 2°C / min; keeping at 1500°C for 1 hour; 1500-600°C at 2°C / min; 600-25°C at 4°C / min.
[0079] (3) Collect the graphitized material and grind it in a mortar.
[0080] (4) The crushed material is acid-leached using concentrated hydrochloric acid (37 wt %) at room temperature to dissolve the iron powder.
[0081] (5) After acid washing, the graphite sample and solution are filtered out using a vacuum filter.
[0082] (6) The filtered sample was washed three times with ultrapure water and then dried at 80 °C for 4 h to obtain the final sample.
[0083] Comparative Example 1
[0084] (1) Take 10 g of pyrolysis oil.
[0085] (2) The sample was placed in a tubular furnace for graphitization under a nitrogen atmosphere. The heating and cooling process was as follows: 25-600°C at 4°C / min; 600-1500°C at 2°C / min; kept at 1500°C for 1 hour; 1500-600°C at 2°C / min; 600-25°C at 4°C / min.
[0086] (3) Collect the graphitized material and grind it in a mortar.
[0087] (4) After washing three times with ultrapure water, the final sample was dried at 80°C for 4 h.
[0088] Effect Example 1: Microstructure
[0089] 1. Test object: graphite negative electrode material obtained in each embodiment
[0090] 2. Test method: The graphite negative electrode materials prepared in each embodiment and comparative example were subjected to X-ray diffraction and Raman tests.
[0091] 3. Test results:
[0092] Figure 2 The X-ray diffraction patterns of artificial graphite of the embodiments and comparative examples are shown. The degree of catalytic graphitization of iron powders in different proportions is shown. The degree of graphitization of embodiment 1 is calculated to be 82.1%, the degree of graphitization of embodiment 2 is 88.3%, the degree of graphitization of embodiment 3 is 93.8%, the degree of graphitization of embodiment 4 is 91.1%, and the degree of graphitization of the comparative example is 73.4%. It can be seen that the control sample (without catalyst) shows a broad diffraction peak, indicating that disordered carbon is formed. It is proved that the pyrolysis oil feedstock is not graphitizable at 1500°C. After adding a small portion of iron powder particles (0.5 times the fixed carbon content), it helps to sharpen the (002) peak and reduce the degree of disorder. With the further addition of iron, the overall diffraction pattern gradually becomes clearer. The intensity of the (002) peak is significantly and gradually enhanced with the increase of the catalyst loading. When iron powder particles with a fixed carbon content of 2 times are loaded, bio-graphite similar to commercial graphite is formed. Further addition of iron particles reduced the crystalline quality of the biographite, especially when loading the iron particles with 3 times the fixed carbon content. Excessive iron loading had a negative impact on the graphitization process, as can be seen from the broader diffraction pattern in the figure.
[0093] Figure 3 is a Raman test graph. It further verifies the results of the XRD test. It can be seen from the figure that each sample shows two characteristic peaks in the D band and the G band. The D band corresponds to the disordered carbon peak, and the G band corresponds to the ordered carbon peak. The higher the peak value of the G band, the higher the degree of graphitization. It can be seen from the figure that Example 3 has the highest degree of graphitization.
[0094] Effect Example 2: Electrochemical Performance
[0095] 1. Test object: graphite negative electrode material obtained in Example 3
[0096] 2. Test method: The graphite negative electrode material obtained in Example 3 was made into a half-cell for testing, as follows:
[0097] (1) Raw materials: The electrode was prepared using 85 wt% of the graphite negative electrode material (active material) obtained in Example 3, 5 wt% of conductive carbon black and 10 wt% of polyvinylidene fluoride (PVDF) binder. The slurry used N-methyl-2-pyrrolidone (NMP) as a solvent.
[0098] (2) Operation process: The fully mixed slurry was coated on the current collector (copper foil) and then vacuum dried at 120 °C for 12 h. The diameter of the punched electrode was 14 mm and had a conductivity of about 3.3 mg cm -2 Loading density of active materials. Metallic lithium (Li) was used as the counter electrode / reference electrode, and 1.2 M lithium hexafluorophosphate (LiPF6) and ethyl methyl carbonate (3:7 wt%) were used as the electrolyte. The half-cell was assembled into a button-type lithium battery in an argon-filled glove box.
[0099] 3. Test results:
[0100] Figure 4 The first and second discharge-charge curves of the artificial graphite negative electrode material prepared in Example 3. It can be seen that when the material is tested at 0.01-2.5V, the 0.1C initial reversible capacity is about 350mAh / g, and the calculated first charge capacity (ICE) is 90.2%. The first charge capacity of bio-graphite is relatively lower than that of commercial graphite (92-94%). This may be due to the different surface composition and area of the surface properties of bio-graphite compared with commercial graphite. The surface composition of synthetic bio-graphite may affect the side reactions between graphite and electrolyte, resulting in the formation of a solid electrolyte interface (SEI), thereby essentially affecting the ICE. The specific data are shown in Table 1 below:
[0101] Table 1 The first and second discharge-charge test data
[0102]
[0103] Figure 5 The cycle life diagram of the prepared artificial graphite negative electrode material. It can be seen that after 120 cycles at 0.1C, the capacity retention rate reaches about 99.4%. The specific data is shown in Table 2 below. Figure 6 The cycle life diagram of the prepared artificial graphite negative electrode material at different discharge rates. It can be seen that the capacity decreases with the increase of the rate in the cycle test at different discharge rates (0.1C-0.2C-0.3C-0.5C-1C-2C-4C-0.1C), but when it returns to the initial rate, the capacity can also be completely restored to the initial capacity. After 90 cycles, the capacity decays, and the capacity retention rate is 99.1%. The specific data is shown in Table 3 below:
[0104] Table 2 Cycle life test data of artificial graphite negative electrode materials
[0105] Number of laps Discharge capacity (mAh / g) Charging capacity (mAh / g) 1 376.6108 348.6113 10 353.6608 349.6608 20 354.9421 350.9421 40 357.9157 353.9157 60 361.3928 357.3928 80 366.0314 364.0314 100 365.6056 363.6056 120 351.538 349.519
[0106] Table 3 Cycle test data at different discharge rates
[0107] Number of laps Capacity (mAh / g) 1 366.0852 10 357.7627 20 360.0546 30 347.5766 40 292.7666 50 58.42681 60 246.8964 70 358.992 80 357.8844 90 354.5428 100 324.5647 。
Claims
1. A method for preparing a graphite material, characterized in that: The method comprises the following steps: graphitizing pyrolysis oil under the action of a catalyst; the fixed carbon content of the pyrolysis oil is 32%-67%; the mass ratio of the catalyst to the fixed carbon content of the pyrolysis oil is (0.5-3):
1.
2. The method for preparing a graphite material according to claim 1, characterized in that: It meets one or more of the following conditions: (1) The mass ratio of the catalyst to the carbon content of the pyrolysis oil is (1-3): 1; (2) The catalyst is iron powder particles; (3) The solid carbon content of the pyrolysis oil is 45%-50%, for example 49.3%; (4) The reaction is carried out in a tube furnace; (5) The reaction is carried out under an inert atmosphere, preferably nitrogen; (6) The temperature of the reaction includes the following heating steps: heating from 25°C to 600°C at a rate of 4°C / min; heating from 600°C to 1500°C at a rate of 2°C / min, and keeping at 1500°C for 1 hour; Cooling from 1500°C to 600°C at a rate of 2°C / min; Cooling from 600°C to 25°C at a rate of 4°C / min; and (7) After the reaction is completed, the following post-processing steps are also included: crushing, acid leaching, filtering, washing, and drying.
3. The method for preparing a graphite material according to claim 2, characterized in that: It meets one or both of the following conditions: (1) The mass ratio of the catalyst to the carbon content of the pyrolysis oil is 2:1; (2) The particle size of the iron powder is ≤10 μm; (3) The acid used for the acid leaching is hydrochloric acid; (4) The acid leaching time is 11-13 hours; (5) The acid leaching temperature is 15-40°C; (6) The filtering method is vacuum filtration; (7) The cleaning is performed with deionized water; (8) The number of cleaning times is 3-5 times; (9) The drying time is 3-5 hours; and (10) The drying temperature is 75-85°C.
4. The method for preparing a graphite material according to claim 3, characterized in that: It meets one or more of the following conditions: (1) The concentration of the hydrochloric acid is 20%-37%; (2) The acid leaching time is 12 hours; (3) The volume ratio of the deionized water used for each cleaning to the sample solution is (2.5-3.5):1; (4) The number of cleaning times is 3 times; (5) The drying time is 4 hours; and (6) The drying temperature is 80°C.
5. The method for preparing a graphite material according to claim 4, characterized in that: It meets one or more of the following conditions: (1) The concentration of the hydrochloric acid is 37%; (2) The volume ratio of the deionized water used for each cleaning to the sample solution is 3:
1.
6. The method for preparing a graphite material according to claim 1, characterized in that: The reaction conditions are any of the following: Scheme 1: Take pyrolysis oil and iron powder particles with a fixed carbon content of 0.5 times the corresponding content, stir and mix them evenly; place the mixed sample in a tubular furnace for graphitization reaction under a nitrogen atmosphere, and the reaction temperature includes the following heating steps: heating from 25°C to 600°C at a rate of 4°C / min, heating from 600°C to 1500°C at a rate of 2°C / min, keeping at 1500°C for 1 hour, cooling from 1500°C to 600°C at a rate of 2°C / min, and cooling from 600°C to 25°C at a rate of 4°C / min; after the reaction is completed, the sample is crushed in a mortar, acid-leached with concentrated hydrochloric acid at 15-40°C, the iron powder is dissolved, filtered with a vacuum filter, washed with deionized water, and dried at 80°C; Scheme 2: Take pyrolysis oil and iron powder particles with a corresponding fixed carbon content of 1 times, stir and mix them evenly; place the mixed sample in a tubular furnace for graphitization reaction under a nitrogen atmosphere, and the reaction temperature includes the following heating steps: heating from 25°C to 600°C at a rate of 4°C / min, heating from 600°C to 1500°C at a rate of 2°C / min, keeping at 1500°C for 1 hour, cooling from 1500°C to 600°C at a rate of 2°C / min, and cooling from 600°C to 25°C at a rate of 4°C / min; after the reaction is completed, the sample is crushed in a mortar, acid-leached with concentrated hydrochloric acid at 15-40°C, the iron powder is dissolved, filtered with a vacuum filter, washed with deionized water, and dried at 80°C; Scheme 3: Take pyrolysis oil and iron powder particles with a fixed carbon content twice that of the corresponding one, stir and mix them evenly; place the mixed sample in a tube furnace for graphitization reaction under a nitrogen atmosphere, and the reaction temperature includes the following heating steps: heating from 25°C to 600°C at a rate of 4°C / min, heating from 600°C to 1500°C at a rate of 2°C / min, keeping at 1500°C for 1 hour, cooling from 1500°C to 600°C at a rate of 2°C / min, and cooling from 600°C to 25°C at a rate of 4°C / min; after the reaction is completed, crush the sample in a mortar, acid-leach with concentrated hydrochloric acid at 15-40°C, dissolve the iron powder, filter with a vacuum filter, wash with deionized water, and dry at 80°C; and Scheme 4: Take pyrolysis oil and iron powder particles with a fixed carbon content three times the corresponding content, stir and mix them evenly; place the mixed sample in a tubular furnace for graphitization reaction under a nitrogen atmosphere, and the reaction temperature includes the following heating steps: heating from 25°C to 600°C at a rate of 4°C / min, heating from 600°C to 1500°C at a rate of 2°C / min, keeping at 1500°C for 1 hour, cooling from 1500°C to 600°C at a rate of 2°C / min, and cooling from 600°C to 25°C at a rate of 4°C / min; after the reaction is completed, the sample is crushed in a mortar, acid-leached with concentrated hydrochloric acid at 15-40°C, the iron powder is dissolved, filtered with a vacuum filter, washed with deionized water, and dried at 80°C.
7. A graphite material, characterized in that: The graphite material is prepared by the method for preparing the graphite material according to any one of claims 1 to 6.
8. Use of the graphite material according to claim 7 as a negative electrode material.
9. A pole piece, characterized in that: It includes the graphite material obtained by the preparation method as claimed in claim 7.
10. A battery, characterized in that: It comprises the pole piece as claimed in claim 9.